2023
DOI: 10.1021/acsbiomaterials.3c01332
|View full text |Cite
|
Sign up to set email alerts
|

Collagen-Binding Nanoparticles for Paclitaxel Encapsulation and Breast Cancer Treatment

Julia Sapienza Passos,
Luciana B. Lopes,
Alyssa Panitch

Abstract: In this study, we developed a novel hybrid collagen-binding nanocarrier for potential intraductal administration and local breast cancer treatment. The particles were formed by the encapsulation of nanostructured lipid carriers (NLCs) containing the cytotoxic drug paclitaxel within a shell of poly( N -isopropylacrylamide) (pNIPAM), and were functionalized with SILY, a peptide that binds to collagen type I (which is overexpressed in the mammary tumor microenvironment) to improve local ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
1
2
0
Order By: Relevance
“…Given that collagen is a predominant component of the tumor microenvironment, and its content and structure are substantially altered by mutations in tumor suppressor genes in cancer cells, collagen affinity provides a strategic avenue for targeted therapy [ 10 ]. Consistent with earlier studies [ 43 , 76 ], we observed that nanoparticles modified with SILY successfully adhered to a collagenous matrix, a property not observed in nonmodified nanoparticles. In line with this finding, the nanoparticles provided longer retention in vivo in the mammary tissue compared to a simple solution.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Given that collagen is a predominant component of the tumor microenvironment, and its content and structure are substantially altered by mutations in tumor suppressor genes in cancer cells, collagen affinity provides a strategic avenue for targeted therapy [ 10 ]. Consistent with earlier studies [ 43 , 76 ], we observed that nanoparticles modified with SILY successfully adhered to a collagenous matrix, a property not observed in nonmodified nanoparticles. In line with this finding, the nanoparticles provided longer retention in vivo in the mammary tissue compared to a simple solution.…”
Section: Discussionsupporting
confidence: 92%
“…The IC 50 values obtained in the spheroids were higher than those obtained in monoculture, which was previously related to the limitation of drug penetration into the spheroid core [ 76 ]. Consistent with the findings observed in monolayer cultures, nanoencapsulation markedly reduced the piplartine IC 50 across both examined cell line spheroids.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation